1983
DOI: 10.1152/ajpendo.1983.245.6.e616
|View full text |Cite
|
Sign up to set email alerts
|

Direct alpha-adrenergic stimulation of hepatic glucose production in human subjects

Abstract: Six normal humans each underwent infusions of 1) saline; 2) propranolol; 3) somatostatin; 4) somatostatin with propranolol; and 5) somatostatin with propranolol plus phentolamine on separate occasions. Propranolol alone had no effect on glucose production or plasma glucose. Somatostatin alone produced the expected initial decrease followed by an increase in both hepatic glucose production and plasma glucose. beta-Adrenergic blockade with propranolol displaced the glucose production (MANOVA, P = 0.0220) and pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
1

Year Published

1984
1984
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 31 publications
2
27
0
1
Order By: Relevance
“…There is considerable evidence that glucagon normally supports postabsorptive glucose production and functions in concert with insulin to maintain the postabsorptive plasma glucose concentration (10,11,13). The present studies were not designed to reassess this concept, but the findings are consistent with it.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…There is considerable evidence that glucagon normally supports postabsorptive glucose production and functions in concert with insulin to maintain the postabsorptive plasma glucose concentration (10,11,13). The present studies were not designed to reassess this concept, but the findings are consistent with it.…”
Section: Discussionmentioning
confidence: 70%
“…Therefore, we hypothesized that adrenergic mechanisms support the postabsorptive plasma glucose concentration and prevent hypoglycemia when glucagon secretion is deficient. In an initial study (13) we found that combined a-and f3-adrenergic blockade blunts the late increase in glucose production and plasma glucose that follows their initial decrease during combined insulin and glucagon deficiency produced by infusion of somatostatin. Adrenergic blockade did not, however, result in a progressive decline in plasma glucose.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although infusions of adrenaline, noradrenaline and salbutamol in normal and insulin-dependent diabetic humans, have, in some studies (Schade & Eaton, 1977Silverberg, Shah, Haymond & Cryer, 1978;Giindogdu, Brown, Juul, Sachs & Sonksen, 1979;Clutter, Bier, Shah & Cryer, 1980;Pernet, Walker & Gill, 1983;Keller, Gerber & Stauffacher, 1984;Bahnsen, Burrin, Johnston, Pernet, Walker & Alberti, 1984;Berk, Clutter, Skor, Shah, Gingerich, Parvin & Cryer, 1985), been shown to cause moderate increases in the blood ketone body concentration, fl-adrenergic blockade has, to our knowledge, not previously been shown to have any antiketogenic effect (Rosen, Clutter, Shah, Miller, Bier & Cryer, 1983;Kosugi, Harano, Nakano, Suzuki, Kashiwagi & Shigeta, 1983;Beylot, Sautot, Dechaud, Cohen, Riou, Serusclat & Mornex, 1985;Oberhaensli, Schwendimann & Keller, 1985), except partially in somatostatin-induced hyperketonaemia (Beaufrere, Beylot, Riou, Serusclat, Cohen, Souquet & Mornex, 1983;Rosen et al 1983). This would indicate that f-adrenergic blockade will normally lower the blood ketone body concentration only in the absence of both insulin and glucagon.…”
Section: Discussionmentioning
confidence: 81%
“…First, the glycemic response to suppression of both endogenous insulin and glucagon (among other effects) with somatostatin is biphasic, with an initial transient decrease in glucose production (3)(4)(5) and the plasma glucose concentration (4 -6), followed by an increase in glucose production (3)(4)(5) and the plasma glucose concentration (4 -6) in healthy humans. While these findings suggest an initial tonic effect of basal glucagon secretion to support the postabsorptive plasma glucose concentration, they suggest that suppression of insulin secretion is the dominant glycemic effect of somatostatin and, therefore, that insulin is the primary determinant of the postabsorptive plasma glucose concentration.…”
Section: Conclusion-thesementioning
confidence: 99%